Traumatic orbital third nerve palsy. Issue 6 (July 2019) - Nagendran, S.T.; Lee, V.; Perry, M.
Abstract: We present a case series of three patients who developed acute traumatic orbital third nerve palsies. To our knowledge, reported cases have mainly been localised to the intracranial course of the nerve and often associated with visual impairment. Those in which the orbit is the site of injury are rare. Our case series highlights the importance of careful preoperative assessment of patients with orbital trauma (particularly when there is a coexisting fracture) and the need to assess ocular movements and pupillary reactions to distinguish between a neurogenic and soft tissue injury. Early diagnosis is helpful in deciding on the timing of the operation and enables patients to be given appropriate counselling to make sure that their expectations are realistic.